2016
DOI: 10.1002/jssc.201600023
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐high performance liquid chromatography with tandem mass spectrometry method for the simultaneous quantitation of five phthalides in rat plasma: Application to a comparative pharmacokinetic study of Huo Luo Xiao Ling Dan and herb‐pair extract

Abstract: A fast, sensitive, and reliable ultra-high performance liquid chromatography with tandem mass spectrometry method has been developed and validated for the simultaneous quantitation and pharmacokinetic study of five phthalides (senkyunolide A, ligustilide, butylidenephthalide, 3-butylphthalide, and levistilide A) in rat plasma after oral administration of Huo Luo Xiao Ling Dan (HLXLD) or Angelica sinensis--Ligusticum chuanxiong herb pair (DG-CX) between normal and arthritis rats. After extraction from blood, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Moreover, double peaks were observed clearly on concentration–time profile with the second peak lower than the first. It is reported that the double peak phenomenon also exist in some other saponins such as mesaconitine, ligustilide . It is well known that drug absorption is a very complex process that manifests itself through potential interaction with a host of physicochemical and physiological variables.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, double peaks were observed clearly on concentration–time profile with the second peak lower than the first. It is reported that the double peak phenomenon also exist in some other saponins such as mesaconitine, ligustilide . It is well known that drug absorption is a very complex process that manifests itself through potential interaction with a host of physicochemical and physiological variables.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the double peak phenomenon also exist in some compounds in nature. As drug absorption is a very complex process that manifests itself through potential interaction with a host of physicochemical and physiological variables [26][27][28]. The detected concentration of savaside A was low after oral TPG, and the parameters of savaside A could not be obtained.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…Furthermore, Q Exactive Focus Orbitrap has a fast positive and negative ion switching function, which can simultaneously detect positive and negative ions when analyzing samples. Therefore, it is a very effective way to realize simultaneously qualitative and quantitative analysis of multiple components [26][27][28][29]. In this study, full mass scan mode equipped with quick switching and dd-MS 2 modules was used, both positive and negative ions (butylidenephthalide, ligustilide and senkyunolide A were detected in positive ion mode, ferulic acid was detected in negative ions mode) were detected in one injection.…”
Section: Introductionmentioning
confidence: 99%